DEVELOPMENT OF HVAC SYSTEM FOR MBSL-2 TFRIC BPPT: For the Comfort and Safety of Testing Personnel and the Safety for the Analysis Process and for the Environment from Exposure to SARS-CoV-2 Virus Contamination - Andhy Muhammad Fathoni; Himawan Sutriyanto; Achmad Maswan; Kanon Prabandaru Sumarah (BRIN, 2021)
Tracing, tracking and testing are keys in fighting COVID-19 pandemic. At the start of the pandemic in Indonesia, the capacity to test with RT-PCR methods as the golden standard was still quite low. BPPT, through TFRIC-19, developed MBSL-2 to increase the capacity of Covid-19 PCR Test. This Mobile Bio-Safety Level-2 (MBSL-2) is equipped with HVAC system which has the main function of providing comfort and safety for testing personnel as well as safety for the testing process. This MBSL-2 also provides safety for the environment in which MBSL-2 is placed from contamination of the SARS-CoV-2 virus which may be released during the PCR analysis process. There are several variants of the Heating, Ventilating and Air Conditioning (HVAC) MBSL-2 that have been built and operated. The requirement and the design result for MBSL-2 has been discussed in this paper. This HVAC system has to be able to cover cooling load of 2459 W. This MBSL-2 HVAC system has been designed to complement the RT-PCR testing facility that is safe for the personnel, environment and testing result from contamination. This MBSL-2 has been proved to be safe in the operation during this pandemic. Keywords : PCR Test; HVAC; COVID-19; MBSL-2, BSL-2